Study on the combination of lime and lignin in the improvement of mechanical properties of loess in Ili area, China - Shichuan Liang; Zizhao Zhang; Xukun Hu; Junyu Jia; Songyuan Lv (PLoS ONE, 2026)
Conventional techniques incorporating either inorganic or organic modifiers alone are insufficient to effectively improve loess roadbeds in practice, thus hindering the development of infrastructure. This study proposes the use of lime-lignin as a modifier for loess improvement. Various mixing samples with different additive dosages (0% lime: 0% lignin, 2% lime: 1% lignin, 4% lime: 2% lignin, 6% lime: 3% lignin, and 8% lime: 4% lignin) were prepared and tested in laboratory experiments and numerical simulations to investigate the mechanical properties of the amended loess. Results showed that the compressive and shear strengths of the modified loess initially increased but then decreased with higher lime and lignin contents, with the most optimal improvement achieved at a lime-to-lignin ratio of 2%:1%. The maximum axial stress in the improved loess is achieved with a lime-to-lignin dosage of 2%:1%, the compressive strength of loess increased by 73.97%.The parameters cohesion (c) and angle of internal friction (φ) reached their maximum values at 2%:1% lime and lignin dosing, with maximum values of 208.35 kPa and 24.23°, which were about 149% higher than that of the natural loess.The numerical simulations validated the laboratory results, demonstrating reduced roadbed settlements and improved stress transfer mechanisms. The formation of a complex three-dimensional network structure by lignin fibers and a cement-soil skeleton by lime hydrate and soil particles collectively enhanced the strength of the soil matrix. The findings of this study provide valuable theoretical references for enhancing loess subgrades.